1980
DOI: 10.1002/smj.4250010106
|View full text |Cite
|
Sign up to set email alerts
|

Short term financial success in large business organizations: The environment‐strategy connection

Abstract: This study examines the interrelationships of environmental changes and strategic action variables with each other and with short term success, for 358 large business firms over a 45 year period. Success (Fortune ratings and ROA) is found to be related to two strategic decision segments.Several strategy‐environment relationships are also found. Some methodological problems are noted in the attempt to move policy research from case analysis to statistical explanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
7

Year Published

1983
1983
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 23 publications
1
52
0
7
Order By: Relevance
“…These findings are consistent with Jauch, Osborn, and Glueck (1980), who employed moderated regression analysis to examine the interacting effects of nine environmental changes on eight strategic decisions and two performance measures. Their results suggested that the interaction of environmental changes and strategic decisions was not significant.…”
Section: Journal Of Hospitality and Tourism Researchsupporting
confidence: 90%
“…These findings are consistent with Jauch, Osborn, and Glueck (1980), who employed moderated regression analysis to examine the interacting effects of nine environmental changes on eight strategic decisions and two performance measures. Their results suggested that the interaction of environmental changes and strategic decisions was not significant.…”
Section: Journal Of Hospitality and Tourism Researchsupporting
confidence: 90%
“…This sector subdivision has been commonly adopted in previous research (e.g. Khandwalla, 1977;Jauch, Osborn, & Glueck, 1980;Tan & Litschert, 1994;Grant, 1998;Jogaratnam, 2005). For the purposes of this study, environmental uncertainty is modeled in terms of three component variables, namely, its hostility, dynamism and complexity.…”
Section: Perceived Environmental Uncertaintymentioning
confidence: 98%
“…The co-alignment theory suggests that the ability of an organisation to adapt to the changing environmental contingencies to 'fit' with the operating context is the key to survival and enhanced performance (Chandler 1962;Jauch et al 1980;Lawrence 1981;Yasai-Ardekani and Nystrom 1996). The effectiveness of the adaptive response is dependent on aligning the response to the environmental circumstances faced by the organisation (Miles and Snow 1978;Hambrick 1983;Lee and Miller 1996;Strandholm et al 2004).…”
Section: Dea Input Variable -Environmental Uncertaintymentioning
confidence: 99%